50. PRACTICE REGARDING HIV/AIDS PREVENTION OF THE PUPILS IN NAMKEUNG HIGH SCHOOL, TONPHEUNG DISTRICT, BOKEO PROVINCE, LAO IN 2023 (Vietnam Journal of Community Medicine, 2025)
Introduction: The study aims to describe the practice regarding HIV/AIDS prevention of the pupils in Namkeung high school in Lao 2023 and its related factors.Methods: This cross-sectional survey was conducted through a self-administered questionnaire on all 357 pupils in Namkeung High SchoolResults: The rate of pupils with good practice regarding HIV/AIDS prevention was 51.1%. This 'good practice' was determined based on a set of criteria that included factors such as the number of sexual partners, sexual intercourse with high-risk groups, condom use, and substance use. Regarding associated factors, grade 12th pupils were 4.5 times more likely to practice HIV/AIDS prevention well than grade 10th pupils (72.7% vs. 37.2%; OR=4.5; 95% CI: 1.5-13.8; p
Keywords: HIV/AIDS; pupils; high school; Lao PDR.